2017
DOI: 10.6007/ijarbss/v7-i6/2964
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Examination for Operational and Credit Risk Perspective – A Case of Commercial Banks of Pakistan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…These studies have concluded that credit risk increases with the growth of nonperforming loans. Ahmed et al (2011);Mehmood et al (2017) also found negative links, which are counterintuitive and contrary to our findings, and have concluded that non-performing loans do not affect credit risk.…”
Section: Analysis and Discussion Of Multiple Regression Collinearitie...contrasting
confidence: 99%
See 2 more Smart Citations
“…These studies have concluded that credit risk increases with the growth of nonperforming loans. Ahmed et al (2011);Mehmood et al (2017) also found negative links, which are counterintuitive and contrary to our findings, and have concluded that non-performing loans do not affect credit risk.…”
Section: Analysis and Discussion Of Multiple Regression Collinearitie...contrasting
confidence: 99%
“…Köhler (2015) and Adusei (2015) found positive correlations and pointed out that the larger the size of the bank results in the greater credit risk. The opposite result, where the size of the banks has no significance and is negatively related to the credit risk, was found by Mehmood, Sheraz, Mehmood, and Mujtaba (2017) in their study of Pakistani banks. NPL -like other independent variables based on the results of the regression equation (see Table 11 shows that there is a positive relationship with credit risk positive correlation between non-performing loans and credit risk has also been found by Busch and Kick (2009); Afriyie (2013) and Alizadeh Janvisloo and Muhammad (2013).…”
Section: Analysis and Discussion Of Multiple Regression Collinearitie...mentioning
confidence: 78%
See 1 more Smart Citation
“…The process of monitoring, estimating and assessing risk is called risk management. According to Mehmood, Sheraz, Mehmood, and Mujtaba (2017) risk is defined in financial terms as the chance that an outcome or investment's actual gain will defer from an expected outcome or return. Risk management is the practice of identifying potential loss or damage (risk) in advance, analyzing them and taking precautionary steps to reduce or curb the risk.…”
Section: Review Of Conceptsmentioning
confidence: 99%
“…Risk management is the practice of identifying potential loss or damage (risk) in advance, analyzing them and taking precautionary steps to reduce or curb the risk. According to Mehmood et al (2017) risk can be classified as non-financial (operating) risk and financial (credit, capital, and liquidity) risks.…”
Section: Review Of Conceptsmentioning
confidence: 99%